2019
DOI: 10.4103/ijnmr.ijnmr_36_18
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nursing intervention integrating an Islamic praying program on labor pain and pain behaviors in primiparous Muslim women

Abstract: Background: Labor pain has always been a priority issue for primiparous women. Pain behaviors appear as a response to labor pain. This study aimed at examining the effect of nursing interventions integrating an Islamic praying (NIIIP) program on labor pain and pain behavior. Materials and Methods: In this experimental design, 42 women in the control group received the usual care; 41 in the experimental group received the usual care and an NIIIP program from the 32 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 19 publications
1
19
0
3
Order By: Relevance
“…Although not generalisable to all women, those from North Africa tend to be less inhibited and more exaggerated in their expression of pain. Many Muslim women are reluctant to use epidural analgesia, often due to lack of knowledge [26]. In the present study, the percentage of Muslim women who received epidural analgesia was 33%.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…Although not generalisable to all women, those from North Africa tend to be less inhibited and more exaggerated in their expression of pain. Many Muslim women are reluctant to use epidural analgesia, often due to lack of knowledge [26]. In the present study, the percentage of Muslim women who received epidural analgesia was 33%.…”
Section: Discussionmentioning
confidence: 46%
“…Eighty-five per cent of the sample did not attend childbirth preparation classes, which could have caused a higher perception of pain, but there is little difference between women from Christian and Muslim cultures in this respect, as the proportion between the two groups was similar. In a study on Islamic women [26], it was shown that those who received pre-birth information had significantly reduced levels of pain during labour. Although Luque-Fernández and Oliver-Reche [25] stated that Muslim women are more vocal when it comes to expressing their pain in labour, in our case the opposite was true, with a greater verbalisation and expression of feelings about the perception of pain being higher for the group of Christian women than for the group of Muslim women, and statistically significant differences were found in this respect.…”
Section: Discussionmentioning
confidence: 99%
“…Positive obedience and religious beliefs that affect Jabodetabek residents, such as praying, performing ablutions, and reading Qur'an, can foster an increasingly caring and comfortable attitude for residents. It can also make people always clean and the soul becomes calm (Desmawati et al, 2019). Spiritual practices and obeying their respective religious teachings can increase endorphins in the body, increase immunity (Ilevbare, Adelowo & Adegbite, 2020), and better protect against pain, disease, and viruses (Desmawati et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…It can also make people always clean and the soul becomes calm (Desmawati et al, 2019). Spiritual practices and obeying their respective religious teachings can increase endorphins in the body, increase immunity (Ilevbare, Adelowo & Adegbite, 2020), and better protect against pain, disease, and viruses (Desmawati et al, 2019). Strong spirituality can strengthen a person's mental and psychology in dealing with this virus (Husni et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…During delivery, in some cultures, women prefer to have someone beside them for support and physical comfort, and they may want to pray or want their companion to pray for spiritual relief (Bohren et al, 2016). Desmawati et al (2019) found that praying during labour alleviates perceived pain in Muslim women. When the spiritual needs of women are not met, they may perceive the delivery process as a traumatic event, and this can make it difficult for them to bond with their infant.…”
Section: Introductionmentioning
confidence: 99%